S107 Genotype-phenotype associations in pulmonary arterial hypertension caused by BMPR2 and EIF2AK4 variants. (15th November 2016) - Hadinnapola, C; Haimel, M; Bleda, M; Bogaard, H; Coghlan, G; Corris, P; Gibbs, S; Kiely, D; Lawrie, A; Peacock, A; Pepke-Zaba, J; Southgate, L; et al.
Abstract : Introduction: Idiopathic pulmonary arterial hypertension (IPAH) is a rare and incurable disease. Causal mutations in BMPR2 are found in 17% of patients. Pulmonary veno-occlusive disease (PVOD) and pulmonary capillary haemangiomatosis (PCH) are rarer forms of pulmonary hypertension and have a worse prognosis. Biallelic mutations in EIF2AK4 have been described in PVOD and PCH. We hypothesised that mutations in these genes are associated with specific phenotypes or endotypes. Methods: Whole genome sequencing was performed on genomic DNA from PAH patients recruited to the NIHR BRIDGE Study (n = 679). Rare (absent from BRIDGE control cohorts [n = 5906] and minor allele frequency < 0.0001 in the ExAC database [http://exac.broadinstitute.org ]) and predicted deleterious (CADD score >15 and Polyphen not benign) variants were selected for association testing with phenotypic and metabolomic data. Plasma samples from 288 patients were sent to Metabolon (USA) for a high-throughput metabolomic screen. Results: Mutations in BMPR2 (82 single nucleotide variants and 13 deletions) were identified in 14% of PAH patients. Unexpectedly, 22 rare and predicted deleterious EIF2AK4 variants were found in 17 patients with IPAH. Biallelic EIF2AK4 variants were found in 1% of patients (5 homozygous variant carriers and 4 potential compound heterozygotes). Additionally, there were 8 heterozygous EIF2AK4 variant carriers in the cohort (1%), suggesting a 3-fold over-representation of heterozygous EIF2AK4 variants compared to ExAC (p = 0.005). BMPR2 mutation carriers presented at a younger age and with more severe pulmonary haemodynamics compared to those without identified variants in the known PAH genes. Biallelic EIF2AK4 variant carriers had a significantly reduced transfer coefficient for carbon monoxide compared to patients with BMPR2 mutations or no identified variants. Heterozygous EIF2AK4 variant carriers were similar to patients with no identified variants. There were no differences between groups in functional class or walk test distances assessed longitudinally. BMPR2 and EIF2AK4 genotype did not influence the plasma metabolome. Discussion: Biallelic EIF2AK4 variants are the second most common genetic defect in patients with apparent IPAH, after BMPR2 . Variants in both genes are associated with characteristic phenotypes. Additional, non-coding variants may be present in heterozygous EIF2AK4 variant carriers. These findings have important implications for the clinical and molecular classification of PAH.